INVESTIGACIONES INTERDISCIPLINARIAS EN LA LLAQTA DE MACHUPICCHU - Bastante Abuhadba, José Miguel (2017)
This article presents a brief description of the Llaqta of Machupicchu, from its scientific discovery in July 1911 to the progress of the research carried out by the Archaeological and Interdisciplinary Research Program in the Sector of the “Manuel Chavez Ballon” Museum (2014) and at the Llaqta of Machupicchu (2015). The discussion includes the reasons why it was built, the size of the permanent population that it could house, cultivated products, and architectural modifications amongst others.